ANALISIS PENDAMPINGAN ORANG TUA TERHADAP SISWA DALAM BELAJAR DI MASA PANDEMI COVID-19 DI SDN 2 NGABUL JEPARA - Suwarno Suwarno (Universitas Muria Kudus, 2023)
This study aims to determine the condition of parents/guardians of students who are not yet technology and information literate in helping children learn during the COVID-19 pandemic. The second goal is for parents to understand their role in assisting their children's learning during the COVID-19 pandemic. Researchers used quantitative methods. While the subject of this research is the parents of students at SDN 2 Ngabul Jepara. In collecting data, researchers used interviews, observations, and documentation. Then the data were analyzed, with two procedures, namely: a) data presentation b) drawing conclusions. The results of this study are a) Parents who do not really understand the development of technology and information find it difficult when accompanying and helping children in learning during the COVID-19 pandemic, so that the assistance is less than optimal. b) The role of parents in accompanying children when studying at home, namely, acting as a companion, motivating, facilitating, and helping to solve problems and being able to create a conducive situation for learning.